ANALYSIS OF SOCIAL ECONOMIC FACTORS AFFECTING INCOME OF RICE FARMERS (Case Study: Purbaganda Village, Pematang Bandar District) Simalungun Regency) - Ricky Efran Ginting (Institute of Computer Science (IOCS), 2020)
This purpose of this study is to analyze the income of rice farmers and to analyze the influence of socio-economic factors on the income of rice farmers in Purbaganda Village, Pematang Bandar District, Simalungun Regency. The research data were obtained from secondary data and primary data. The data analysis method used in this research is to use income analysis and multiple linear regression test. The results showed that the average income of rice farmers was Rp. 43,732,927.78/harvest season and the total expenditure or cost in one production was Rp. 9,223,313.89 and the average income of rice farmers was Rp. 34,509,613. ,89/harvest season. Socio-economic factors that affect the income of rice farmers are the experience factor (X3), land area (X4), labor (X5) and cost (X6) which have a real or significant effect on the income of rice farmers.